TRANSFER TEKNOLOGI DEHUMIDIFIER BOX UNTUK MENGATASI PERMASALAHAN KUALITAS MADU PADA MADU ARWANA - Rahmahwati, Ratih; Yanti, Hikma; Uslianti, Silvia (Universitas Mataram, 2024)
The partner in this PKM program is the Arwana Forest Honey business group engaged in marketing of Kapuas Hulu forest honey. The observations on Arwana Honey partners revealed several problems, including high water content in forest honey originating from Danau Sentarum, Kapuas Hulu District. Based on these problems, partners need help in the form of a device that reduces the water content of honey in the form of a dehumidifier box that can reduce the water content of forest honey. Besides that, based on the results of observations and discussions, problems were also encountered in the field of marketing management for Arwana Honey. The solution offered by the PKM team is through marketing management training including marketing training, packaging, labeling and logo visual design improvements. The results of PKM activities are (1) Increased knowledge of partner groups, especially in terms of improving the quality of honey and marketing management; and (2) there is an improvement in the quality of honey by reducing the water content in honey.